2020
DOI: 10.3390/foods9060707
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and Hypoglycaemic Effect of Wholemeal Bread with Amaranth (Amaranthus dubius Mart. ex Thell.) on Sprague Dawley Rats

Abstract: The effect of consuming breads made with wheat flour and Amaranth (Amaranthus dubius Mart. ex Thell.) wholemeal flour on Sprague Dawley rats with hyperlipidaemia and hyperglycaemia induced through feeding was studied. Four diets were provided: control (CD: Ratarina®), commercial bread (CBD), bread with 100 g·kg−1 (ABD10) and 200 g·kg−1 (ABD20) amaranth flour. Zoometric and blood chemistry parameters were measured before and after consuming the diets. A completely random factorial design of 2 × 4 × 2 was used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Based on the available data on therapeutic applications of Amaranthus species in the pharmaceutical industry, it seems that further effort should be put into the separation and characterization of active compounds with therapeutic potential (Yong et al, 2019). As a result, Amaranthus dubius has the potential to be a future crop for a variety of purposes and to alleviate malnutrition, especially in developing countries where the plant is underutilized (House et al, 2020;Sánchez-Urdaneta et al, 2020). In light of the above, we investigated secondary metabolites of Amaranthus dubius in different solvent extracts as well as the free radical scavenging properties of the solvent extract with strong secondary metabolite material (Ajayi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the available data on therapeutic applications of Amaranthus species in the pharmaceutical industry, it seems that further effort should be put into the separation and characterization of active compounds with therapeutic potential (Yong et al, 2019). As a result, Amaranthus dubius has the potential to be a future crop for a variety of purposes and to alleviate malnutrition, especially in developing countries where the plant is underutilized (House et al, 2020;Sánchez-Urdaneta et al, 2020). In light of the above, we investigated secondary metabolites of Amaranthus dubius in different solvent extracts as well as the free radical scavenging properties of the solvent extract with strong secondary metabolite material (Ajayi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has a dietary fibre content of around 12 g%, which reduces the digestibility of the grain, but provides satiety. It has a high vitamin E content, which acts as an antioxidant, protecting the fatty acids it provides [8], of which 50% correspond to polyunsaturated fatty acids (omega 6) and 25% to monounsaturated fatty acids (omega 9) [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sánchez-Urdaneta et al fed rats with breads made with amaranth (Amaranthus dubius Mart. ex Thell) flour and observed that consumption of amaranth-enriched bread enhanced lipid profiles of rats and prevented metabolic and cardiovascular diseases due to its hypoglycemic and hypolipidemic effects [4]. Moreover, an in vivo study revealed that phenylpropanoid extract from Halosarcia indica (Willd.)…”
Section: Introductionmentioning
confidence: 99%